Otimização do processo de extrusão de ração padrão para tilápias do nilo (Oreochromis niloticus) - Dalcin, Marina Osmari (2020)
This study aimed to evaluate different extrusion conditions, temperature and humidity of standard feed containing corn starch and fish meal as macro nutrients, as well as the physical- chemical and technological properties of the extrudates in addition to the evaluation of apparent digestibility in Nile tilapia. . The best extrusion condition was established using a central rotational composite design with outlet temperature (92 - 138 ° C) and humidity (15 - 39%) as independent variables, and buoyancy and available starch content as an answer. Through this experimental planning, 11 tests were carried out. The highest content was found in experiment 1, in which 100°C was used as the outlet temperature and 15% humidity. Through the images obtained by scanning electron microscopy, the presence of pores of different sizes is noted, with a predominance of pores of small diameter, indicating good expansion and development of starch. Subsequently, the apparent digestibility coefficients of dry matter (DM), crude protein (CP), mineral matter (MM), organic matter (OM) and ether extract (EE) of two diets were determined, one in extruded form and the other, pelleted for Nile tilapia specimens, both diets with the same nutritional composition. Digestive indexes and digestive enzyme activities were evaluated. Twelve specimens of Nile tilapia were randomly distributed in six incubators (200 L), the experimental design was completely randomized, with two treatments and three replications. The data were subjected to analysis of variance and the means compared by Student's t test (P<0.05). There was no statistical difference in the parameters evaluated, except in the centesimal composition of the diets (DM, MM and EE) and feces (CP), and the apparent digestibility coefficient of ether extract. In short, both diets, both extruded and pelleted using the same procedures employed, can be used for Nile tilapia, without interfering with the evaluated parameters. It is worth emphasizing that the extrusion process, under the conditions tested, improved the digestibility of the protein, reducing the excretion of this nutrient through the feces compared to the pelleted diet.